ARTICULATION LEARNING EFFECTS IN READING SKILL AT ISLAMIC EDUCATION STUDENTS OF ISLAMIC UNIVERSITY OF KUANTAN SINGINGI - Puspa Gundary; Gusparia Gusparia (Ensiklopedia Education Review, 2025)
The research was carried out in Islamic Education (PAI) University of Kuantan Singingi. It started   14 April 2025 at Study Program of Islamic Education . The data collection techniques in this research are observation, test and documentation. The samples of this research were 62 students, consist of 31 students as control class (PAI IA) and 31 students as experimental class (PAI IB). The instrument used to collect the data is test (Pre test and Post test) The subject of this statistic analysis that tcount is 2.141 and ttable is -2.000, because tcount is 2.141 ttabel is -2.000. so the conclusion is that Ho is rejected and hypothesis alternative (Ha) is accepted. The final result of the students’ ability in reading recount text is taken from experimental class and the characteristic is good. The results of this research is “There is a significant The Effect Of Using Articulation Learning Model Toward Students’ Reading Skill at Islamic University of Kuantan Singingi ”. Keywords: Articulation Learning Model, Reading, Skill